Promoting “Safe Speeds” Behaviour by Changing the Conversation Around Speed and Speeding - Ian Johnston; Eric Howard (Journal of Road Safety)
Traditional speed limit setting and speed enforcement practices created a community norm which historically accepted, indeed valued, low-level speeding. Public education strategies to date have largely focussed on conveying crash risk and casualty consequences and have lacked credibility. The approach required stems from preventive medicine and is analogous to promoting inoculation; something everyone needs to do to protect the community as well as themselves. Elements of a proposed new strategy are outlined.